PENINGKATAN KEMAMPUAN GURU DALAM MENYUSUN RPP MELALUI BIMBINGAN BERKELANJUTAN DI SDN 10 NANGA TAYAP - Suripto, Suripto (Universitas Tanjungpura, 2019)
The first stage in learning according to the standard process is learning planningthat is realized by the preparation of the Implementation Lesson Plan. In theframework of implementing the 2013 curriculum, teachers must prepare lessonplans by adjusting some components to the curriculum documents. There are some teachers who are confused when they have to formulate lesson plans because the subjects taught are different from their educational background, it has an impact on the failure of the learning process and also inhibits the improvement of the quality of the school itself. The problem solving that is applied in this research is to provide continuous guidance to the teacher in creating lesson plans. This study uses two rounds of action research. Each round consists of four stages: designing, implementing, observing, and reflecting. The targets of this study are all teachers at SDN 10 Nanga Tayap. The data obtained in the form of observations of teaching and learning activities. From the results of the analysis it was found that the ability of teachers in arranging lesson plans has increased from cycle I to cycle II, that is, cycle I in the range of 109, with quite good categories, and in the second cycle in the range of 152 with very good categories. The conclusion from this study is that the method of sustainable guidance can positively influence the ability of teachers in preparing lesson plans at SDN 10 Nanga Tayap.